Recyclable Palladium-Catalyzed Carbonylative Coupling of 2-Iodoanilines, Trimethyl Orthoformate, and Amines: A Practical Synthesis of Quinazolin-4(3H)-ones - Li, Jianying; Zhou, Zebiao; Xie, Gang; Cai, Mingzhong (Synthesis, 2022)
An efficient heterogeneous palladium-catalyzed carbonylative annulation of 2-iodoanilines, trimethyl orthoformate, and amines has been developed. The reaction proceeds smoothly in toluene at 110 °C using N,N-diisopropylethylamine (DiPEA) as base and 2 mol% of MCM-41-anchored bidentate phosphine palladium complex [MCM-41-2P-Pd(OAc)2] as catalyst under 10 bar of carbon monoxide and provides a general and practical method for the construction of a wide variety of quinazolin-4(3H)-ones in good to excellent yields from commercially easily available starting materials. This heterogenized palladium catalyst can be easily recovered via a simple centrifugation process and reused more than nine times with almost consistent catalytic efficiency.
Keywords: palladium; multicomponent reaction; carbonylative coupling; quinazolinone; heterogeneous catalysis